ANALISIS POTENSI ELEKTABILITAS PARTAI KEADILAN SEJAHTERA PADA PEMILU 2014 DI KOTA SEMARANG - M Ikhmal Hisham Rizaldy; Budi Setyono; Supratiwi . (Journal of Politic and Government Studies, 2014)
This study was conducted to explain how Partai Keadilan Sejahtera chance to win the 2014 legislative elections in the city of Semarang, both in the scale of the vote and of seats in Parliament in Semarang. The things will be the basis of the observations is the target of the vote and seats as well as a political marketing strategy ahead of the 2014 elections Partai Keadilan Sejahtera in Semarang, strengths and weaknesses of the Partai Keadilan Sejahtera party in Semarang city today, as well as the level of community support for Partai Keadilan Sejahtera Semarang.This study will use a mixed methods or qualitative-quantitative where researchers will use qualitative methods to collect the data written and spoken words of research subjects and informants. In addition, researchers using quantitative methods that manifested by the use of a questionnaire to measure the level of community support numerically.The results showed that the Partai Keadilan Sejahtera chair set acquisition with an estimated 8-12 vote totals for voice 80000-100000. Partai Keadilan Sejahtera try to focus on winning the election and local scale by using a personalized approach and promotion strategies of candidates through various media to attract the support of the community Semarang. They are quite benefited with the large popularity of competent candidates and candidate - though also have the problem of the threat and the level of materialism abstentions Semarang people. Primarily, they are optimistic to achieve the targets that they have created. However, their optimism does not correspond with the level of community support for Partai Keadilan Sejahtera Semarang. Because, the Semarang people are not too keen to choose Partai Keadilan Sejahtera due to various reasons such as more interested in choosing the other party and the notion that politics is full of corruption. Furthermore, this study only found Partai Keadilan Sejahtera loyalist sympathizers and minimal amounts.Keywords : Political Parties, legislative elections, political marketing.